Symbiotic relationship between Polyporus umbellatus and Armillaria gallica shapes rhizosphere bacterial community structure and promotes fungal growth - Zhou, Lingfeng; Liu, Liu; Gao, Weiwei; Li, Bing; Guo, Shunxing (Frontiers in Microbiology, 2025)
AimsPolyporus umbellatus sclerotium, known for its diuretic properties, relies on a symbiotic association with Armillaria for its growth and quality development. However, the impact of soil microorganisms on this symbiosis remains uncertain and warrants investigation. The primary objective of this research is to characterize the microorganisms capable of enhancing the symbiotic interaction between Armillaria gallica and Polyporus umbellatus sclerotia in the rhizosphere soil.MethodsSymbiotic cultivation experiments were conducted in woodland habitats with four groups: symbiotic group (Z0), control group (Z1), A. gallica-only group (Z2), and P. umbellatus-only group (Z3). Rhizosphere soil community profiling analysis was conducted using high-throughput sequencing of the bacterial 16S rRNA gene. Subsequently, bacterial strains were isolated, purified, and back-inoculated with A. gallica to assess their effects on this symbiotic relationship.ResultsA total of 10,009 operational taxonomic units (OTUs) were identified, with the symbiotic group (Z0) showing higher bacterial richness and diversity (ACE, Chao1, Shannon indices) compared to Z2 and Z3. Dominant phyla such as Proteobacteria, Acidobacteriota, and Bacteroidota were notably more abundant in Z0. Notably, Rhodococcus sp. Z2-1 significantly promoted A. gallica rhizomorph growth (diameter increased by 112.2%, branches by 160.9%) and symbiosis establishment (100% contact rate in inoculated pots vs. 0–22.2% in controls).ConclusionThe symbiotic relationship between P. umbellatus and A. gallica shapes rhizosphere bacterial communities, with specific bacteria like Rhodococcus sp. enhancing fungal growth and symbiotic efficiency. This study presents the potential for developing a bio-bacterial fertilizer for cultivation of medicinal material.